2013
DOI: 10.3390/ijms14059440
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rice NADPH Oxidase Genes and Their Expression under Various Environmental Conditions

Abstract: Plasma membrane NADPH oxidases (Noxs) are key producers of reactive oxygen species under both normal and stress conditions in plants. We demonstrate that at least eleven genes in the genome of rice (Oryza sativa L.) were predicted to encode Nox proteins, including nine genes (OsNox1–9) that encode typical Noxs and two that encode ancient Nox forms (ferric reduction oxidase 1 and 7, OsFRO1 and OsFRO7). Phylogenetic analysis divided the Noxs from nine plant species into six subfamilies, with rice Nox genes distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 50 publications
13
95
0
Order By: Relevance
“…Six groups of orthologs were identified (Figure 2), which is in agreement with previous evolutionary analyses of plant Rbohs [34]. The VvRboh sequences were distributed amongst all groups (Figure 2): VvRbohA, VvRbohB, VvRbohC1, VvRbohE and VvRbohH belong to group V, III, II, IV and VI, respectively, while VvRbohC2 and VvRbohD belong to group I.…”
Section: Resultssupporting
confidence: 87%
“…Six groups of orthologs were identified (Figure 2), which is in agreement with previous evolutionary analyses of plant Rbohs [34]. The VvRboh sequences were distributed amongst all groups (Figure 2): VvRbohA, VvRbohB, VvRbohC1, VvRbohE and VvRbohH belong to group V, III, II, IV and VI, respectively, while VvRbohC2 and VvRbohD belong to group I.…”
Section: Resultssupporting
confidence: 87%
“…In plants, NADPH oxidases (respiratory burst oxidase homologs, Rboh ) play key roles in generating ROS by catalysing the conversion of O 2 to superoxide (O 2 ‐ ) (Suzuki et al , ). The rice genome encodes nine Rboh proteins (A–I) (Wang et al , ) of which OsRbohA , OsRbohB and OsRbohE are reported to be involved in ROS production during pathogen invasion (Wong et al , ; Yoshie et al , ). To verify the impact of auxin signalling on OsRboh ‐mediated ROS levels, the expression of OsRboh transcripts was monitored in auxin signalling mutants.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of only monocot Rboh (Potamogeton crispus PcRboh1) present in this cluster has not been identified yet. In the case of cluster 6, out of six proteins in sub-cluster 6A, only two (OsRbohB and OsRbohH) were reported to be drought-induced (Wang et al 2013; Kaur and Pati 2016). We hypothesize that other monocot Rbohs (ZmRbohF, ZmRbohl, HvRbohBl and HvRbohB2) may function in abiotic stress.…”
Section: Discussionmentioning
confidence: 99%